Estudio de la influencia de la fertilizacion nitrogenada y la iluminacion sobre atributos morfologicos y fisiologicos de brinzales de Q.suber L. CULTIVADO EN VIVERO. RESULTADOS DEL 1er. AÑO EN CAMPO - Martínez Romero, G; Planelles González, R; Zazo Muncharaz, J; Bela Quero, D; Vivar Sanz, A; López Arias, M (III Congreso Forestal Español Congreso, 2001)
This essay studies the influence of fertilization and illumination of Q.suber L. in container seedlings. Plants were tested in three diferents levels of fertilization (control substrate, fertilizated substrate and fertilizated substrate plus nitrogen supplied) with two of illumination (full light conditions and a reduction of 50% illumination). After the first year in nursery, plants was installed in survey parcels, where growing measures and survival rates were studied
Keywords: Cork oak; fertilization; ilumination; Quercus suber L.

Inflación del capital natural de la dehesa: hipótesis sobre la naturaleza caótica de la seca de los Quercus DENTRO DEL PROCESO DE LA SENESCENCIA FOLIAR - CUEVAS, S; TORRES, E; VÁZQUEZ, F.Mª.; López Arias, M; HERNÁNDEZ, A (III Congreso Forestal Español Congreso, 2001)
“Dehesa” is a gap forest yielding as an ecological-economic system (money-borrowed), poor soils (money-lender) upheld during optimal stopping millenia. Have supported multiple antropogenic nutrition disturbances during chaotic and resource routine affecting oak root uptake. Shoot nutrient odyssey is represented by cobweb model as price (nitrogen) evolution working by-product quantity (biomass). This trial evaluates cork oak (Quercus suber L.) and holm oak (Quercus rotundifolia Lam.) harvest basic sustainability (HBS) or nitrogen leaf redemption, southern Extremadura situated, evaluating ecological economic orientor for ecosystem. Defective HBS management hypothesis is expound in the absence of forest management, leading to sickly phenomenon on forest health as oak decline. Parallelly, HBS is proposed as an cork quality indirect index. Leaf senescence fork leads to physiological imbalance and, in some final cases, whole canopy defoliation (tie break). K.W.: Cobweb model, Oak decline, Renewal, Optimal stopping Dehesa, Nitrogen.
Keywords: Cobweb model; nitrogen; Oak decline; Optimal stopping Dehesa; Renewal